2018
DOI: 10.1177/0284185118795322
|View full text |Cite
|
Sign up to set email alerts
|

The nerve root sedimentation sign in diagnosis of lumbar spinal stenosis

Abstract: Background The nerve root sedimentation sign is a magnetic resonance (MR) sign, shown to be present in central lumbar spinal stenosis. The lack of sedimentation of the nerve roots to the dorsal part of the dural sac is consistent with the positive nerve root sedimentation sign. Purpose To validate the reliability of the nerve root sedimentation sign in diagnosis of different grades of lumbar spinal canal stenosis. Material and Methods This study was a retrospective review of 101 consecutive MR imaging (MRI) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…In addition, the CSA of dural sac, as spinal canal area parameter, was superior to vertebral canal diameter line parameters in diagnosing LSS [18], due to the characteristics of the spinal canal morphology, some degenerative changes occur in the non-midline part of the spinal canal often induced lateral recess stenosis and nally lead to reduction in spinal canal volume [18]. However, some researcher considered that the CSA could be insu cient as a diagnostic tool [19,20]. Lohman et al [21] con rmed that the degree of LSS and the CSA of the dural sac had no signi cant correlation with the severity of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CSA of dural sac, as spinal canal area parameter, was superior to vertebral canal diameter line parameters in diagnosing LSS [18], due to the characteristics of the spinal canal morphology, some degenerative changes occur in the non-midline part of the spinal canal often induced lateral recess stenosis and nally lead to reduction in spinal canal volume [18]. However, some researcher considered that the CSA could be insu cient as a diagnostic tool [19,20]. Lohman et al [21] con rmed that the degree of LSS and the CSA of the dural sac had no signi cant correlation with the severity of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The nerve root sedimentation sign was first described in LSS patients in the supine position by Barz et al 1 The sedimentation sign could be used as a supplemental diagnostic method of LSS because it can differentiate patients with severe LSS from asymptomatic patients while having the strength of being easily observed on MRI images [1][2][3]5]. In asymptomatic patients, gravity was thought to be responsible for the sedimentation of nerve roots to the dorsal part of the dural sac.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since the discovery of this sign, several studies have demonstrated the high sensitivity and specificity of the sedimentation sign for severe lumbar spinal stenosis (LSS). [2][3][4][5] This sign is most often present in stenotic patients who need surgery. 6 A positive sedimentation sign may change to a negative sign following adequate surgical decompression of stenotic lumbar levels.…”
Section: Introductionmentioning
confidence: 99%
“…After this original work, a number of studies consistently suggested that SedSign was a powerful tool in the differential diagnosis for LSS [7][8][9]. Such a view, however, was questioned by some researchers that a positive SedSign was merely suggestive of severe LSS [10,11] and the capability of SedSign in differentiating LSS from nonspeci c back pain was limited [12,13,11]. Although the inconsistent ndings may be due to patient sampling [11] and varied de nitions of stenosis and severity [14,13], it is important to note that such controversies re ected, more or less, the poor understanding of the mechanism leading to positive SedSign.…”
Section: Introductionmentioning
confidence: 99%